Syed Muhammad Naquib Al-Attas' Contributions to Malay World Studies: An Appraisal - Sabjan, Muhammad Azizan (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
Professor Dr. Syed Muhammad Naquib al-Attas is one of the most prominent, multifaceted and creative Muslim thinkers in contemporary times who embodies the multi-disciplinary mastery and unity, personal integrity and courage of the Islamic religious-intellectual ideals which were genuinely represented by numerous Muslim scholars, sages and saints of the past, especially Abū Hamid Muhammad al-Ghazālī (d.505/1111). His contributions to scholarly works especially Malay World Studies are manifold. To date, he has written more than 24 books and monographs in English and Malay, many of which have been translated into other languages such as Arabic, Persian, Turkish, Urdu, Malayalam, Indonesian, German, Russian, Bosnian, Japanese, Hindi and Korean. Among his publications: Rangkaian Ruba'iyyat, Some Aspects of Sufism as Understood and Practiced among the Malays, Raniri and the Wujudiyyah of 17th Century Acheh, The Mysticism of Hamzah Fansuri, A Comment on the Hujjatu'l Siddiq of Nur al-Din al-Raniri. This paper attempts to explore his contributions to Malay World Studies with a specific reference to his influence in shaping the development of Malay Studies in Malaysia and Southeast Asia. Keywords: Syed Muhammad Naquib al-Attas, Malay World studies, Islamic scholar, Islamization